First record of Leptodactylus caatingae Heyer & Juncá, 2003 (Amphibia, Anura, Leptodactylidae) for the Ceará State, Brazil - Vieira, Jânia Brito; Magalhães Junior, Arnaldo José Correia; Silva, Guilherme Ramos da; Machado, Luiz Cezar; Nicola, Patrícia (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2012)
Leptodactylus caatingae was described by Heyer & Juncá (2003), based on specimens collected in Bahia. The species is known in the Caatinga and Atlantic Rainforest biomes, in the states of Bahia, Pernambuco, Paraíba, and Espírito Santo. Here, we report the first record of L. caatingae for the state of Ceará.